Kabir seen through the eyes of the people: Reception, adaptation and transcreation - Rajbhar, Veeru (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Kabir seen through; the eyes of the people; Reception; adaptation; and transcreation